2020
DOI: 10.1002/pbc.28706
|View full text |Cite
|
Sign up to set email alerts
|

Features and outcome of chronic myeloid leukemia at very young age: Data from the International Pediatric Chronic Myeloid Leukemia Registry

Abstract: Introduction: Chronic myeloid leukemia (CML) is rare in the first two decades of life comprising only 3% of newly diagnosed pediatric and adolescent leukemias. We studied the epidemiologic and clinical features of patients with CML diagnosed at younger than 3 years of age and evaluated treatment and long-term outcome. Method: Data from the International Pediatric I-BFM/CML Registry were retrospectively analyzed using the European LeukemiaNet criteria of the year 2006. Characteristics and treatment outcome of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The significant delay in achieving CHR in under‐5 children is similar to the cohort from the I‐BFM pCML registry, showing delayed attainments of milestones in under‐3 children. Nonetheless, the rate of attaining MMR was comparable to older children in both the cohorts 26 . Aggressive nature of the disease and difficulty in dosing imatinib in younger children may be one of the reasons for a delayed response during the initial phase of treatment.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The significant delay in achieving CHR in under‐5 children is similar to the cohort from the I‐BFM pCML registry, showing delayed attainments of milestones in under‐3 children. Nonetheless, the rate of attaining MMR was comparable to older children in both the cohorts 26 . Aggressive nature of the disease and difficulty in dosing imatinib in younger children may be one of the reasons for a delayed response during the initial phase of treatment.…”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, the rate of attaining MMR was comparable to older children in both the cohorts. 26 Aggressive nature of the disease and difficulty in dosing imatinib in younger children may be one of the reasons for a delayed response during the initial phase of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to current recommendations, vaccinations with live vaccines are completed by the age of 4-6 years in most countries. As CML is rarely seen in children below that age, only very few children face the issue of live vaccine administration during TKI treatment [27][28][29]. A problem exists for older children who missed their booster vaccinations, as well as an increasing number of children whose parents generally have refused vaccination (e.g., the measles vaccine) [27,28,30].…”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%
“…In the first two decades of life, CML is extremely rare, with reported incidences of 0.7/million/year in infancy to 1.2/million/year in adolescents 4,5 . Epidemiological studies conducted in the previous millennium reported poor survival with conventional chemotherapy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…1 In the first two decades of life, CML is extremely rare, with reported incidences of 0.7/million/year in infancy to 1.2/million/year in adolescents. 4,5 Epidemiological studies conducted in the previous millennium reported poor survival with conventional chemotherapy. 6 Hydroxyurea (HU) and interferon-alfa (IFN-α) reduced the proliferation of leukemia cells but did not improve long-term survival.…”
mentioning
confidence: 99%